Education on Hydroponic Technology to Increase the Productivity of Modern Farmers - Rohaeti, Rohaeti; Nurhayati, Sri (Journal of Education Research, 2023)
The study investigates the impact of education on hydroponic technology among modern farmers, contributing to a deeper understanding of the educational implications involved. The study employed a qualitative methodology, utilising in-depth interviews and observations as data collection techniques. The participants consisted of ten farmers residing in Desa Sukamanah Pangalengan. The implementation of a complete hydroponic curriculum, together with the utilisation of varied training methodologies, has provided farmers with the necessary tools and knowledge to facilitate the shift from conventional agricultural practises to hydroponics. Education enhanced their comprehension, bolstering self-assurance and fostering sustainable, high-caliber farming methodologies. This study highlights the crucial role of education in the adoption of novel practises and contributes to the ongoing dialogue on developments in agriculture. The results indicate that there is a need to broaden educational programmes to reach a larger audience, which can be achieved through partnerships and the utilisation of online platforms.